The Relevancy of the Presidential System in Nepal - Bhandari, Naresh (NPRC Journal of Multidisciplinary Research, 2025)
Background: Nepal’s federal parliamentary system, established by the 2015 constitution, has been marred by persistent political instability, frequent government changes, and governance deficits. This has led to widespread public disillusionment and sparked a serious debate, including within recent political movements, on the viability of adopting a presidential system as an alternative. Objective: This study aims to critically evaluate the shortcomings of Nepal’s parliamentary system and analyze the justifications for, and potential of, a presidential system to address issues of political stability, policy effectiveness, and governmental accountability. Methods: The research employs a qualitative methodology, relying on secondary sources. It conducts a comparative and theoretical analysis of parliamentary and presidential systems, drawing on both international academic literature and national discourse from Nepali scholars and commentators. Findings: The analysis indicates that the presidential system presents a contextually relevant and potentially viable alternative for Nepal. It is theorized to offer greater political stability and direct executive accountability. However, its successful implementation is contingent upon robust constitutional checks and balances to mitigate risks of authoritarianism and executive-legislative deadlock. Conclusion: While the presidential system emerges as a compelling alternative to the unstable parliamentary model, its adoption in Nepal would require careful institutional design, including strong balancing mechanisms and strengthened constitutional bodies, to ensure its democratic functioning. Novelty: This paper provides a timely and comprehensive analysis of the presidential system debate in post-constitution Nepal, synthesizing global theoretical perspectives with specific insights from Nepal’s unique socio-political context.